Sistem Informasi Penjualan Baju Berbasis Web Menggunakan Metode Agile PadaToko Cakayu.id - Yusuf Rio Pambudi; Harjunadi Wicaksono (PT Pustaka Cendekia Group, 2024)
This study aims to design and implement a web-based sales information system to improve operational efficiency and transaction data accuracy. The approach used is the Agile software development method with the stages of plan, design, develop, test, release, and feedback. Data were obtained through observation, interviews, and literature review. The results show that the developed system is able to automate the ordering process, transaction recording, and present product information in real time, thereby minimizing transaction errors while facilitating customer interaction with the store. In addition, this system allows for structured sales data recording that can be used for analysis and business decision-making. Thus, the application of Agile methods in the development of a web-based sales information system has proven effective in addressing Toko Cakayu.id's operational problems and has a positive impact on improving service quality and business competitiveness. An abstract is a brief summary of the paper to help readers quickly identify the main research problem, the solution to the problem encountered, the research objectives, and the preliminary results, which can be presented in numbers or percentages, depending on the research needs. The abstract should be clear and informative, stating the research problem and its solution. The abstract should be between 90 and 230 words long